Introduction - Peter A. Joy (Washington University Journal of Law & Policy, 2014)
The legal profession and law schools have been in the throes of major changes since the financial crisis came to a head in 2008. This volume of the Journal of Law and Policy, ―New Ideas in Law and Legal Education,‖ primarily focuses on recommendations for and developments in legal education, to respond to the changing legal environment. To put these Articles and Essays in context, it is helpful to consider some of the changes in the legal profession and in law schools over the past five years. When the financial crisis hit in 2008, conventional wisdom initially held that the downturn in law firm and government hiring of lawyers would be temporary. Many people who lost their jobs and who had been considering law school decided to apply. This initial surge in law school applications resulted in first-year enrollments at American Bar Association (ABA)-accredited law schools rising in 2009 and then topping out at 52,500 for the Fall 2010 entering class. When lawyer hiring did not pick up, news articles began to lament the fact that there appeared to be too many lawyers, too many law schools, and that attending law school was a bad investment. As hiring remained weak and worries about law school debt rose, the 2011 entering class size fell to 48,700, and the class size fell again to 44,500 students for the 2012 entering class. Although the final numbers for the 2013 entering class are not in, predictions are that the class size will shrink further. This has led commentators to predict that some law schools will close within the next decade. As law schools face the challenge of declining enrollment, they also face the need of preparing students better for the practice of law today and the legal needs of clients tomorrow.
Keywords: legal education; new ideas